A taxonomic review of the Australian genus Eurylychnus Bates (Coleoptera: Carabidae: Broscini) - Lay, Stuart (Zootaxa, 2023)
The Australian genus Eurylychnus Bates, 1891 is reviewed and its eight species are redescribed. A key to species is provided together with illustrations of their habitus and male genitalia. Lectotypes are designated for Eurylychnus cylindricus Sloane, 1916 and Eurylychnus kershawi Sloane, 1915.